Hypoglycemic of Cajanus scarabaeoides in glucose overloaded and streptozotocin-induced diabetic rats - Pattanayak, Suman; Nayak, Siva Shankar; Panda, Durgaprasad; Shende, Vikas (Bangladesh Journal of Pharmacology, 2009)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">In light of traditional claim of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Cajanus scarabaeoides (L)<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> in the treatment of diabetes, we studied the effects of different solvent extracts in normal, glucose over loaded normal and streptozotocin-induced diabetic rats. The methanolic extract (500 mg/kg orally) was produce significantly reduce blood glucose level at normal, glucose over loaded normal rats, and streptozotocin-induced diabetic rats 15 days treatment whereas petroleum ether and chloroform extract (500 mg/kg orally) did not exhibit any significant effect on three groups of rats. Histopathology studies on pancreas streptozotocin-induced diabetic rats inflammatory changes were detected in pancreatic islets results from selectively destroy of insulin producing <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-eudc-font-family: 'Times New Roman'; mso-latinext-font-family: 'Book Antiqua'; language: el; mso-ansi-language: el; mso-bidi-language: ar-SA;" lang="el">beta<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">-cells. These changes are inhibited by <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">C. scarabaeoides<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> methanolic extract and gliclazide. The antidiabetic activity of methanolic extract may be due to the presence of flavonoids.